Community Characteristics of Brown Planthopper (Nilaparvata lugens Stal) Predator Arthropoda Community in Agroforestry-Based Rice Fields - Dadi Dadi (Budapest International Research and Critics University, 2020)
This study aims to explore the potential of agroforestry ecosystems in maintaining the balance of the rice field ecosystem. Two rice fields around agroforestry with different types of agroforestry were selected, namely rice fields adjacent to simple agroforestry and complex agroforestry in Gunungcupu Village, Sindangkasih District, Ciamis Regency, West Java. Arthropod species data were obtained using a mask and suctioning was carried out with an aspirator. There are 40 sample plots at each Location. Plots were placed systematically in rice fields adjacent to agroforestry with a distance between plots of 10 m and a distance between plots of 10 m. Observations were made since the beginning of the first planting period, September 20 2018, continued during the planting interval and ended in the last week of the second planting period on June 14 2019. Based on the analysis results, it was found that the even distribution of predatory arthropod species in the rice fields was not affected by the planting period. The planting interval also did not affect the diversity and even distribution of insect predatory arthropod species. This condition indicates that agroforestry areas have the potential to support the diversity of arthropod species in paddy fields.